Human trafficking: the international, Malaysian legal framework and Shariah perspectives - Abddul Hamid, Zuraini; Mokhtar, Khairil Azmin (International Islamic University Malaysia, 2013)
Slavery and forced labour have been accepted to be against humanity. These practices are expressly prohibited by the Federal Constitution in Malaysia. Although the prohibition of human trafficking is not expressly mentioned in the Constitution, it could be regarded as one of the most heinous crimes according to the letter, intent and spirit of the constitution. This is related to the fact that human trafficking is much associated with modern day slavery and therefore is against the ideology of the Malaysian nation and acceptable norms of the international community and Islamic law and Shariah values. The paper will explore the available international human rights and the laws governing human trafficking in Malaysia. The research is based on the current situation and cases of human trafficking in Malaysia. By understanding and observing these, it will help to conclude that trafficking has violated human rights and governing laws in Malaysia. The paper also looks at Islamic law perspectives on human trafficking, and to a certain extent, the stand taken by Muslim countries on the issue. The paper is mainly a conceptual and doctrinal discussion combined with critical legal analysis of certain laws in Malaysia. It will also involve some comparative elements with some Muslim countries where necessary.